2015
DOI: 10.1111/hepr.12519
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism in minimal hepatic encephalopathy assessed by 3.0‐Tesla magnetic resonance spectroscopy

Abstract: A quantitative analysis of this phenomenon using MRS may contribute to an early and objective diagnosis of MHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Patients with chronic liver disease often develop various types of complications . The brain show evidence of metabolic disorder in cirrhotic patients with no overt hepatic encephalopathy . Covert hepatic encephalopathy (CHE) is a neurocognitive complication of chronic liver disease and is considered the mildest form of the clinical spectrum of hepatic encephalopathy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic liver disease often develop various types of complications . The brain show evidence of metabolic disorder in cirrhotic patients with no overt hepatic encephalopathy . Covert hepatic encephalopathy (CHE) is a neurocognitive complication of chronic liver disease and is considered the mildest form of the clinical spectrum of hepatic encephalopathy .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The brain show evidence of metabolic disorder in cirrhotic patients with no overt hepatic encephalopathy. 4 Covert hepatic encephalopathy (CHE) is a neurocognitive complication of chronic liver disease and is considered the mildest form of the clinical spectrum of hepatic encephalopathy. [5][6][7] Recently, we reported that CHE is seen in approximately 30% of cirrhotic patients in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In the human studies using MRS, Gln levels in the brains of cirrhotic patients were also significantly higher than in healthy controls and were correlated with peripheral blood ammonia concentrations in cirrhotic patients with or without HE. [15][16][17] The elevated production of Gln was shown to have pathological significance by stimulating ROS production, which leads to ammonia-induced astrocyte swelling and, finally, inhibition of neurotransmission. 3,15,41 Therefore, the inhibition of intracellular Gln levels by L-CA co-treatment, as shown in the present study, may be a critical mechanism by which L-CA protects astrocytes against hyperammonemia.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10] Physiologically, astrocyte-neuron interactions play roles in mitigating oxidative stress resulting from cytotoxic Gln. [11][12][13] However, pathologic conditions such as ammonia-overloaded astrocytes induced excess Gln, 14 and the increased level of Gln creates an osmotic gradient, resulting in astrocyte swelling through the imbalance of the intracellular Gln-Glu complex and myo-inositol, [15][16][17] leading to numerous alterations, such as a disturbance of energy metabolism, oxidative stress, imbalance of neurotransmitters, and redistribution of cerebral blood flow. 3 Therefore, control of hyperammonemia is critically important in patients with HE.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperammonemia finally induces the swelling of astrocytes, which is the only compartment for the detoxification of ammonia released by the synthesis of glutamine (Gln) in the brain, resulting in a disturbance of neurotransmission [16][17][18]. Many studies, using 1 H-magnetic resonance spectroscopy, have supported astrocyte swelling and Gln accumulation in the brain in cirrhotic patients with or without HE [18][19][20]. Furthermore, some recent studies have also shown that gut dysbiosis is closely associated with the pathogenesis of HE in LC [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%